Đặt biểu thức trên là A, ta có:
A = 1 x 2 + 2 x 3 + 3 x 4 + 4 x 5 + ... + 49 x 50
=> 3A = 3 x (1 x 2 + 2 x 3 + 3 x 4 + 4 x 5 + ... + 49 x 50)
=> 3A = 1 x 2 x 3 + 2 x 3 x 3 + 3 x 4 x 3 + 4 x 5 x 3 + ... + 49 x 50 x 3
=> 3A = 1 x 2 x (3 - 0) + 2 x 3 x (4 - 1) + 3 x 4 x (5 - 2) + 4 x 5 x (6 - 3) + ... + 49 x 50 x (51 - 48)
=> 3A = 1 x 2 x 3 - 0 x 1 x 2 + 2 x 3 x 4 - 1 x 2 x 3 + 3 x 4 x 5 - 2 x 3 x 4 + 4 x 5 x 6 - 3 x 4 x 5 + ... + 49 x 50 x 51 - 48 x 49 x 50
=> 3A = 49 x 50 x 51
=> A = 49 x 50 x 51 : 3
=> A = 41650